(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the theories of second language acquisition through an in-depth analysis of two learner profiles and the instructional approaches applied to support their language development. Drawing on sociocultural theory, Krashen’s Input Hypothesis, and contemporary perspectives on identity, motivation, and investment, the study examines how individual differences—including learning styles, linguistic backgrounds, personal identities, and socio-cultural contexts—shape learners’ language acquisition processes. Two students, Abbos and Dilnoza, are described in detail to illustrate how factors such as motivation, bilingualism, exposure to English, family environment, and personal interests influence their progress. The article further discusses pragmatic and syntactic challenges faced by learners, instructional adaptations, and the role of CLIL, CLT, and behaviourist methods in supporting skill development. The author’s teaching philosophy emphasizes student-centered learning, culturally responsive pedagogy, and the integration of technology, highlighting how theoretical principles guide classroom practice. Overall, the paper demonstrates how understanding learners’ identities and motivations can enhance effective second language instruction.